The Birthday Party is “Comedy of menace” - Ismail Radam, Halima (International Journal of Psychosocial Rehabilitation, 2020)
Harold Pinter (1930-2008) is a great modern British dramatist . The label , a comedy of menace , was first used in 1957 by David Campton¹ in the subtitle of his play “The Lunatic Vie" and was a year later applied to the plays of Pinter in a magazine article. This is certainly an appropriate title for The Birthday Party. A comedy of menace is a play in which the laughter of the audience in some or all situations is accompanied, or immediately followed, by a feeling of some impending disaster. Throughout such a play , the audience feels uneasy even while laughing because of its perception of some threat , explicit or implicit, to the principal character and to the audience itself. In other words, the audience is made aware , in the very midst of its laughter , of some menace. The menace proceeds from potential or actual violence in the play or from an underlying sense of violence throughout the play. Or the menace may proceed from a feeling of uncertainty and insecurity. The play has different elements of the drama; it is, therefore, metaphysical and also symbolical. The play seems to have no story as such . However , if one dives deep , one will be able to find the different levels of meaning in the play.